Traffic calming study : the effectiveness of various types of speed humps - Muhammad Farhan, Abd. Karim (2012)
Traffic calming is defined as a device that will reduce the speed of the vehicle at a certain places. There are many types of traffic calming devices such as speed humps, roundabouts, semi dividers, street closures, and chicane deviation. Generally in residential area in Malaysia, the most widely traffic calming devices that been used in order to reduce vehicles' speed is speed humps. There are many types of speed humps has been design and vary according to its shapes, dimensions, and condition of application. This study is carried out to determine the effectiveness of various type of speed humps to reduce vehicles' speed. The types of speed humps that been analyze are speed humps, transverse bar, and the combination of speed humps and transverse bar. The research and data collection will be conducted at a residential area in Kuantan. To determine the spot speed of the vehicles that going through those speed hump, Radar Gun will be used. The vehicles' spot speed will be read before, on, and after the they gone through those speed humps. The delay of time taken for the vehicles passing the speed humps also will be recorded. After sufficient data and amount of samples has been taken, the data will be analyze using one way ANOVA and Microsoft Excel. The analysis that been conducted will come to the conclusion on which types of traffic calming devices is the most effective one in order to reduce speed and to increase delay and the results obtained is the combination of the speed hump and transverse bar for the most effective in reducing the vehicle speed and cause the longest duration of delay.